Protecting the right of the poor in the process of nullity of a marriage - BARTCZAK, ADAM (Prawo Kanoniczne, 2013)
Human dignity is the basis of the human rights. The law can’t discriminate anyone of various factors, especially on his economic situation. The legislatives of the process of nullity of a marriage are including legal norm concern to the poor. They are located in the Code of Canon Law and in the Instruction Dignitas connubii. This regulation determines the possibility of exemption from payment of court fees and gives free legal aid. The article shows the conditions necessary to provide assistance to the poor, the entity issuing the decision and the effects of application of the law. We are dealing with the protection of the rights, but not soften the law.